Bahasa Inggris - Siska Noer Avifah; Arum Sekar Wulandari; Ika Roostika; Yusuf Sigit Ahmad Fauzan (Postgraduate, University of Mataram, 2026)
Callus induction in kluwih teak wood represents a crucial stage of indirect plant propagation through somatic embryogenesis. This study aims to examine the effect of a combination of 2,4-D and kinetin on callus induction from three propagule types: leaf, petiole, and stem derived from in vitro culture. A completely randomized factorial design was applied with two factors: propagule type and medium formulation. The medium consisted of 2,4-D and kinetin combinations at concentrations of 0.00, 0.50, 1.00, 1.50, and 2.00 mg/L. Variables observed included propagules survival, percentage of callus formation, initiation time, proportion of propagules forming callus, texture, color, and fresh weight of callus. Significant interactions between explant type and medium formulation were observed for the percentage of callus formation, initiation time, and callus color. In contrast, the survival rate, proportion of callus-forming explants, and callus fresh weight were influenced by single factors. Leaf explants cultured in a medium containing 0.5 mg/L 2,4-D plus 0.5 mg/L kinetin achieved the highest callus formation rate and the fastest initiation, producing friable callus with a yellowish-white appearance, so that the combination was identified as the most effective treatment for in vitro callus induction of kluwih teak wood.